Rancang Bangun Hidroponik Dengan Bantuan Pompa Bertenaga Surya - Fikri Dinegoro; Rusnam Rusnam; Eri Gas Ekaputra (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
Agriculture traditionally still uses large areas of land with relatively large amounts of water. The application of solar energy is one of the uses of new and renewable energy. This research uses a 50 Wp photovoltaic cell, battery, solar charge controller, DC stepdown, DC pump and hydroponic frame. The stages of the research are the design of the tools, the calculation of the power required by the tools, the manufacture of the tools, the collection of data and the analysis of the data. The data collected is temperature, sunlight intensity, electric power, electrical energy, water discharge, and photovoltaic efficiency. The data were processed and analyzed in an exploratory manner. Based on the results of the research conducted, the lowest average temperature was 25.33 C and the highest was 33.70 C with the highest average light intensity of 920.26 w/m2 at 12.00 WIB. The relationship between temperature and light intensity with a value of R2 of 0.7594. The highest average electrical energy obtained by polycrystalline is 30.44Wh. The water lost from the hydroponic system is 0.03%. The efficiency of photovoltaic cells is 10.09%–15.72%.         Keywords:  DC pump, hydroponics, light intensity, photovoltaic